Gastrointestinal Bleeding during Continuous-Flow Left Ventricular Assist Device Support is Associated with Lower Rates of Cardiac Transplantation. Issue 6 (November 2015) - Holley, Christopher T.; Harvey, Laura; Roy, Samit S.; Cogswell, Rebecca; Eckman, Peter; Liao, Kenneth; John, Ranjit
Abstract : Gastrointestinal bleeding (GIB) remains a significant problem after continuous-flow left ventricular assist device (CF-LVAD) implantation. We hypothesized that the subsequent need for blood transfusions in patients with GIB may reduce rates of cardiac transplantation. We performed a retrospective review of 232 patients implanted with the HeartMate II (HM II) CF-LVAD from June 2005 through May 2013 at our center to determine risk factors for GIB and assess its effect on cardiac transplantation. Over a total LVAD follow-up time of 364 person-years, 62 GIB episodes occurred in 49 patients (27%), for an event rate of 0.45 gastrointestinal bleeds/patient-year of LVAD support. Women made up 15% of our cohort, yet contributed 29% of the GIB ( p = 0.06). Survival at 6 month, 1 year, and 2 years was not statistically different in patients who developed GIB and those who did not (77% vs 78%, 74% vs 71%, and 61% vs 54%, respectively). In transplant-eligible patients, GIB was associated with a 27% lower rate of cardiac transplantation (rate ratio 0.73, p < 0.05). Although the mechanism behind this finding is unclear, GIB appears to be linked to higher transfusion rates, which may cause the development of subsequent allosensitization.